Dopamine Suppresses Osteogenic Differentiation of Rat Bone Marrow-Derived Mesenchymal Stem Cells via AKT/GSK-3β/β-Catenin Signaling Pathway - Zhili Kuang; Zheng Chen; Shaoqin Tu; Zhihui Mai; Lin Chen; Xiaoning Kang; Xiaochuan Chen; Jiaming Wei; Yuxuan Wang; Yun Peng; Hong Ai (Stem Cells International)
Nervous system is critically involved in bone homeostasis and osteogenesis. Dopamine, a pivotal neurotransmitter, plays a crucial role in sympathetic regulation, hormone secretion, immune activation, and blood pressure regulation. However, the role of dopamine on osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (rBMSCs) remains poorly understood. In this study, we firstly investigated the effect of dopamine on the apoptosis, proliferation, and osteogenic differentiation of rBMSCs. Dopamine did not, however, interfere with the apoptosis and proliferation of rBMSCs. Interestingly, dopamine suppressed the osteogenic differentiation of rBMSCs, as characterized by reduced ALP staining, ALP activity, mineralized nodule formation, and the mRNA and protein levels of osteogenesis-related genes (Col1a1, Alp, Runx2, Opn, and Ocn). Furthermore, dopamine inactivated AKT/GSK-3β/β-catenin signaling pathway. Treatment of LiCl (GSK-3β inhibitor) rescued the inhibitory effects of dopamine on osteogenic differentiation of rBMSCs. LY294002 (AKT inhibitor) administration exacerbated the inhibitory effects of dopamine on osteogenic differentiation of rBMSCs. Taken together, these findings indicate that dopamine suppresses osteogenic differentiation of rBMSCs via AKT/GSK-3β/β-catenin signaling pathway. Our study provides new insights into the role of neurotransmitters in bone homeostasis.